Seminar Daring Mengenai Pembelajaran Berbasis Stem Bagi Guru Paud - Tita Hasanah; Wardianti; Yulfa Arizqiyani (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2022)
Online seminars or commonly called webinars on STEM (Science, Technology, Engineering, Mathematics) learning for early childhood teachers are one of the community service activities that aim to enrich knowledge in implementing learning for students to build 21st century skills. This activity was held through the Zoom Meeting platform, attended by 39 participants who work as early childhood teachers in Bogor Regency, with a duration of 240 minutes. The implementation of the activities took place well, smoothly and orderly. It is hoped that this webinar activity can be continued with offline training or workshops so that teachers can implement the theory through various activities that are suitable for early childhood.